THE EFFECT OF ZAKAT FUNDS ON INCREASING MUSTAHIK INCOME AN INDONESIA IN 2013-2024: A BIBLIOMETRIK ANALYSIS USING VOSVIEWER - Suhaemi, Suhaemi; Amin, Muhammad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The objective of this study is to review and evaluate the development of trends and topics regarding mustahik income. The methodology employed in this study is a bibliometric analysis approach. Data collection was conducted with the assistance of the Google Scholar database through Publish or Perish. The results yielded 141 articles for the period 2013-2024 with the keyword mustahik income. The accurate results were then carried out through VOSviewer. The results indicated a notable increase in the number of scientific publications on mustahik income from 2013 to 2024. Over the course of the study period, there was a surge in research articles on the income of mustahik in 2021 and 2024, with 76 articles published in these years. Visualization of the data using VOSviewer reveals 49 items, grouped into eight clusters with 381 links and a total link strength of 923. This topic has been extensively researched, yet there is considerable scope for further investigation, particularly in relation to other keywords such as the amount of zakat funds, business capital, and the length of business. These areas offer promising avenues for future research in the field of zakat.